2021
DOI: 10.1002/ece3.8027
|View full text |Cite
|
Sign up to set email alerts
|

Strong isolation by distance among local populations of an endangered butterfly species (Euphydryas aurinia)

Abstract: The marsh fritillary (Euphydryas aurinia) is a critically endangered butterfly species in Denmark known to be particularly vulnerable to habitat fragmentation due to its poor dispersal capacity. We identified and genotyped 318 novel SNP loci across 273 individuals obtained from 10 small and fragmented populations in Denmark using a genotyping‐by‐sequencing (GBS) approach to investigate its population genetic structure. Our results showed clear genetic substructuring and highly significant population differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Despite the clear patterns of genetic structure present in this species, F ST values between populations of Hayden's ringlets were low to moderate. The scale of differentiation we observed is consistent with fine‐ to moderate‐scale genetic population structure ( F ST between 0.01 and 0.2) seen in other non‐migratory butterfly species (Hinojosa et al., 2023; Pertoldi et al., 2021; Talla et al., 2019, 2023), and on average greater than in migratory species like monarchs (FST=0.0001) (Talla et al., 2020). While the F ST values we observed may be considered low in other groups of organisms, in many cases F ST values between nominal species of butterflies are not considerably greater than what we found within populations of the Hayden's ringlet (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the clear patterns of genetic structure present in this species, F ST values between populations of Hayden's ringlets were low to moderate. The scale of differentiation we observed is consistent with fine‐ to moderate‐scale genetic population structure ( F ST between 0.01 and 0.2) seen in other non‐migratory butterfly species (Hinojosa et al., 2023; Pertoldi et al., 2021; Talla et al., 2019, 2023), and on average greater than in migratory species like monarchs (FST=0.0001) (Talla et al., 2020). While the F ST values we observed may be considered low in other groups of organisms, in many cases F ST values between nominal species of butterflies are not considerably greater than what we found within populations of the Hayden's ringlet (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…This approach has been implemented for a British population of the Marsh Fritillary, Euphydryas aurinia (Rottemburg, 1775) (Nymphalidae) (Table 1). The species is a Eurasian butterfly with declining populations across its range (Petenian et al, 2005) and multiple studies have found metapopulation structure in E. aurinia (Warren, 1994;Anthes et al, 2003;Davis et al, 2021;Junker et al, 2021;Pertoldi et al, 2021;Konvicka et al, 2023). Population sizes fluctuate as a result of pressure from parasitoid wasps (Porter, 1983).…”
Section: Microsatellite Markers In Lepidopteran Conservation: Relevan...mentioning
confidence: 99%
“…Strong subpopulation structure and recent range expansion may confound local signatures of adaptation, and therefore analytical approaches should take this into account (e.g., Stuart et al, 2022d ; 2022c ). The impact of separate introduction sites or range expansions on population-wide genetic variation is something that may need to be considered not just within invasive populations, but during genomic studies on non-invasive populations (e.g., Drury et al, 2017 ; Drinan et al, 2018 ; Pertoldi et al, 2021 ), and species reintroductions (e.g., Kaulfuss & Reisch 2017 ; Dincă et al, 2018 ; Mims et al, 2019 ).…”
Section: Perspectives From the Study Of The European Starlingmentioning
confidence: 99%